Dependency of Nonlinearity on Design Parameters in SAW Devices - Forster, Thomas; Chauhan, Vikrant; Mayer, Markus; Mayer, Elena; Mayer, Andreas; Ebner, Thomas; Wagner, Karl; Hagelauer, Amelie (IEEE MTT-S International Conference on Microwave Acoustics and Mechanics, IC-MAM 2022, 2022)
This work focuses on the dependencies between typical design parameters of surface acoustic wave (SAW) resonators and the nonlinear emitted signals of second and third order. The parameters metalization ratio and pitch are used as examples, but the approach can be extended to other design parameters as well. It is shown, that the interaction between the nonlinear current generation and the linear admittance is defining the measured nonlinear power signals. It is also discussed, that changes in linear properties get more pronounced in nonlinear responses. Therefore, slight effects on linear parameters will have significant influence on the observed nonlinearity.
CRIS-Team Scopus Importer:2023-03-08